Choroidal melanoma metastasizing to maxillofacial bones - Pandey, Manoj (BioMed Central, 2007)
BACKGROUND: Melanomas are malignant neoplasm of melanocytic origin, commonly seen on skin and various mucous membranes. Melanomas are the commonest intraocular malignant tumour in the adults. CASE PRESENTATION: A 50-year-old female presented with complains of painless progressive swelling in right cheek region of two months duration. Examination revealed a 6 × 4 cm bony hard swelling in right zygomatic region near and below lateral canthus of right eye with loss of vision. Investigations revealed it to be a choroidal melanoma metastatising to the zygomatic bone. Patient was successfully treated by surgery. CONCLUSION: Choroidal melanoma, which commonly metastasizes to liver and lungs, never involves the lymph nodes and metastasis to facial bones is rare. Here we report a case of choroidal melanoma metastasizing to maxillofacial bones.